PENGARUH PENGGUNAAN MEDIA KONKRET TERHADAP PEMAHAMAN KONSEP PERKALIAN SISWA KELAS IV DALAM PENDIDIKAN MATEMATIKA SEKOLAH DASAR - Nurhaswinda; Mutia Nanda; Muhammad Arif (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study addresses the low level of students’ understanding of multiplication concepts in elementary mathematics education, which is often caused by abstract teaching methods and limited use of concrete learning media. The objective of this research is to examine the effect of using concrete media on students’ conceptual understanding of multiplication in elementary school. This study employed a quantitative approach with a quasi-experimental design, involving two groups: an experimental class that utilized concrete media and a control class that applied conventional teaching methods. The participants were fourth-grade students selected through purposive sampling. Data were collected through pre-test and post-test instruments designed to measure students’ conceptual understanding of multiplication. The results of the study indicate that students who learned using concrete media showed a significant improvement in their understanding compared to those who received traditional instruction. The findings suggest that the use of concrete media enhances students’ engagement and facilitates better comprehension of abstract mathematical concepts. Therefore, integrating concrete learning media is recommended to improve the quality of mathematics learning in elementary education.